REGROWTH AND YIELD Asystasia gangetica Subsp.Micrantha FERTILIZED UREA BY SUBSTITUTION OF COW MANURE FERTILIZER - R., Handayani; Witariadi, N. M.; Wirawan, I W. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of substitution of urea fertilizer with cow manure fertilizer on regrowth and yield of Asystasia gangetica subsp. Micrantha. This research was conducted in the greenhouse of Sading Village, Mengwi District, Badung Regency. This study lasted for three months, using a complete randomized design (RAL) consisting of 5 treatments and repeated four times each, resulting in 20 experimental units. The treatment of substitution of urea fertilizer with cow manure fertilizer is: 0 tons ha-1 (D0), 20 tons ha-1 cow manure (D1), 200 kg urea ha-1 (D2), 150 kg urea ha-1 + 10 tons ha-1 cow manure (D3), and 100 kg urea ha-1 + 15 tons ha-1 cow manure (D4). The observed variables were growth variables, yield variables, and plant growing characteristic variables. The results showed that the substitution of urea fertilizer with cow manure increased the variables of plant height and number of branches. It was concluded that the substitution of urea fertilizer with cow dung can increase the regrowth of plants Asystasia gangetica Subsp. Micrantha on the variables of plant height and number of branches. Treatment with a dose of cow dung fertilizer of 20 tons ha-1 can substitute urea fertilizer to produce regrowth and the best results in plants Asystasia gangetica Subsp. Micrantha.